Designing with Computational Intelligence - Nedjah, Nadia; Lopes, Heitor Silvério; Mourelle, Luiza de Macedo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book discusses a number of real-world applications of computational intelligence approaches. Using various examples, it demonstrates that computational intelligence has become a consolidated methodology for automatically creating new competitive solutions to complex real-world problems. It also presents a concise and efficient synthesis of different systems using computationally intelligent techniques.
On Using Fuzzy Logic to Control a Simulated Hexacopter Carrying an Attached Pendulum -- Monocular Pose Estimation for an Unmanned Aerial Vehicle using Spectral Features -- Simultaneous Navigation and Mapping in an Autonomous Vehicle based on Fuzzy Logic -- Fully Scalable Parallel Hardware for Wheeled Robot Navigation using Fuzzy Control -- Nonlinear Correction for an Energy Estimator Operating at Severe Pile-up Conditions -- Non-Supervised Learning Applied to Analysis of Topological Metrics of Optical Networks -- Mole Features Extraction for a Melanoma Recognition System -- Human-Machine Musical Composition in Real-Time Based on Emotions Through a Fuzzy Logic Approach -- A Recursive Genetic Algorithm-based approach for Educational Timetabling Problems -- Evolving Connection Weights of Artificial Neural Network Using a Multi-Objective Approach with Application to Class Prediction -- Diversification Strategies in Evolutionary Algorithms: Application to the Scheduling of Power Network Outages -- WBdetect: Particle Swarm Optimization for Segmenting Weld Beads in Radiographic Images.
Keywords: Computational intelligence; Artificial intelligence; Computer-aided engineering; Engineering design; Computational Intelligence; Artificial Intelligence; Computer-Aided Engineering (CAD, CAE) and Design; Engineering Design